2020
DOI: 10.1016/j.envres.2020.109848
|View full text |Cite
|
Sign up to set email alerts
|

Heat related mortality in the two largest Belgian urban areas: A time series analysis

Abstract: BackgroundSummer temperatures are expected to increase and heat waves will occur more frequently, be longer, and be more intense as a result of global warming. A growing body of evidence indicates that increasing temperature and heatwaves are associated with excess mortality and therefore global heating may become a major public health threat. However, the heat-mortality relationship has been shown to be location-specific and differences could largely be explained by the most frequent temperature. So far, in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Baccini et al (2008) found a daily maximum temperature associated with the minimum mortality rate at 23.3 °C in Western Europe cities [ 6 ], 21.8 °C, 23.9 °C, and 24.1 °C in Zurich, London, and Paris, respectively. In a previous investigation carried out in Belgium in the cities of Antwerp and Brussels [ 18 ], minimum risk thresholds were observed at a daily maximum of 25.2 °C and 22.8 °C, respectively (considering a lagged average of 0–3 days) while Martinez et al (2018) considered a minimum mortality at 26.0 °C for daily maximum temperature in Antwerp [ 17 ]. In the present study, the temperature–mortality relationships were separately investigated in nine agglomerations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baccini et al (2008) found a daily maximum temperature associated with the minimum mortality rate at 23.3 °C in Western Europe cities [ 6 ], 21.8 °C, 23.9 °C, and 24.1 °C in Zurich, London, and Paris, respectively. In a previous investigation carried out in Belgium in the cities of Antwerp and Brussels [ 18 ], minimum risk thresholds were observed at a daily maximum of 25.2 °C and 22.8 °C, respectively (considering a lagged average of 0–3 days) while Martinez et al (2018) considered a minimum mortality at 26.0 °C for daily maximum temperature in Antwerp [ 17 ]. In the present study, the temperature–mortality relationships were separately investigated in nine agglomerations.…”
Section: Discussionmentioning
confidence: 99%
“…The association between cold and mortality may also change with global warming and this is not well understood [ 12 , 13 , 14 , 15 ]. Most studies investigating the temperature–mortality relationship mainly focused on the effects of heat on all-cause mortality as in Belgium [ 16 , 17 , 18 ] where cold-related mortality nor cause-specific temperature–mortality relationships have been properly investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general increase in hot days (days with a maximum air temperature above 30 °C) is driven by climate change and poses a major health threat to city dwellers (Schuster et al, 2017;De Troeyer et al, 2020). The intensity of the urban heat island effect is strongly dependent on the urban structure, such as the number and distribution of green infrastructure (Kumar et al, 2019;Sinha et al, 2021) and the degree of sealing.…”
Section: Environmental Stressors In the Study Areamentioning
confidence: 99%
“…Urban citizens are exposed to additional heat stress due to the urban heat island with warmer near-surface air temperature in urban centers compared to the surrounding areas. As the urban dwellers are unable to recover from extreme temperature during daytime, the urban heat island (UHI) effect can be particularly detrimental to public health during heat waves (De Troeyer et al 2020). Land-use and land-cover changes (LULCC) are expected to strongly impact climate warming trajectories in the near future (Cugnon et al 2019;IPCC 2019;Kuang 2020b).…”
Section: Introductionmentioning
confidence: 99%